Nutritional requirement and its role on honeybee: a review - Pudasaini, Rameshwor; Dhital, Bigya; Chaudhary, Smiriti (Journal of Agriculture and Natural Resources, 2020)
Honey bees play significant role in crop pollination. As, honeybee nutrition is raising global topic in beekeeping, it’s essential nutrients, nutrient sources and role in honey bees are reviewed in this paper. Like other animals, honeybees also need carbohydrate, protein, vitamins, minerals and water. These nutrients are primarily supplemented by pollen, nectar, royal jelly or water. Adequate supplement of these nutrients play significant role in growth and development in honeybees and also development of immunity in honeybees. Knowledge of bee nutrition helps to manage nutrient in bee colony and prevents them from different diseases and pests.